Design and application of an intelligent management application program for patients with an ostomy (造口人士智慧管理APP的设计与应用) - GAN Xingliang (甘星亮); SUN Min (孙敏); WANG Can (王灿) (中西医结合护理)
A specialist nursing alliance was established based on the local professional committee of ostomy. According to the analysis of preoperative, postoperative and home-based healthcare needs and management of postoperative complications, an intelligent management application program for patients with a colostomy was designed. This intelligent management application program consisted of five function modules: patient education center, preoperative self-efficacy evaluation; postoperative follow-up, online clinic, home-based care. (以造口专业委员会为平台, 搭建专科护理联盟, 在分析造口患者术前、术后、居家全流程实际需求及术后并发症观察和处理的基础上, 设计并开发造口人士智慧管理APP。此APP包含患教中心、术前效能自评、术后随访、在线问诊、居家护理五大模块。)